2021
DOI: 10.3390/ma14133584
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Raman, Brillouin and Nd3+ Photo Luminescence Spectroscopy to Distinguish the Effect of Uniaxial Stress from Cooling Rate on Soda–Lime Silicate Glass

Abstract: Evolution of spectroscopic properties of a soda–lime silicate glass with different thermal history and under applied uniaxial stress was investigated using Raman and Brillouin spectroscopies as well as Nd3+ photoluminescence techniques. Samples of soda–lime silicate with a cooling rate from 6 × 10−4 to 650 K/min were prepared either by controlled cooling from the melt using a differential scanning calorimeter or by a conventional annealing procedure. Uniaxial stress effects in a range from 0 to −1.3 GPa were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…While their controlled formation can be exploited for the generation of periodic gratings, they can also act as undesirable scatter centres in waveguides or can reduce the strength of laser welded glass interfaces 41,42 . Since the interaction mechanism between laser radiation in the ps‐ to fs‐range and glass is still barely understood, alternative approaches for structural analysis of the modified zones are needed 43,44,45 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While their controlled formation can be exploited for the generation of periodic gratings, they can also act as undesirable scatter centres in waveguides or can reduce the strength of laser welded glass interfaces 41,42 . Since the interaction mechanism between laser radiation in the ps‐ to fs‐range and glass is still barely understood, alternative approaches for structural analysis of the modified zones are needed 43,44,45 …”
Section: Resultsmentioning
confidence: 99%
“…41,42 Since the interaction mechanism between laser radiation in the ps-to fs-range and glass is still barely understood, alternative approaches for structural analysis of the modified zones are needed. 43,44,45 Periodic modifications ca. 500 μm below the surface of a GeO 2 -Na 2 O-glass which have been induced by ps-laser micromachining (average power: 1.5 W, repetition rate: 2 MHz, mark speed: 20 mm/s) were investigated via nano-CT (Figure 10A).…”
Section: High-aspect-ratio Cantilever Beamsmentioning
confidence: 99%
“…Further study with Raman spectroscopy (Figure 3b) revealed that all visible bands are also characteristic of glass. Namely, the bands with maxima at 1183, 1097, and 954 cm −1 can be attributed to the Q 4 , Q 3 , and Q 2 modes of Si-O stretching vibrations, the wide and low-intensity band around 794 cm −1 is related to Si vibration in its tetrahedral oxygen cell, and bands at lower wave numbers are caused by Si-O-Si bending vibration modes, including from the rings of three Si around 570-600 cm −1 [51][52][53][54][55]. Many of the band's characteristics of W-O-W and O-W-O in various modifications of WO 3 , such as those with maxima around 800-820 cm −1 , 650 cm −1 , and 320-330 cm −1 , overlap with glass bands.…”
Section: Characterization Of the Grown Wo 3 Filmsmentioning
confidence: 99%